The Students’ Misconceptions in Using Three-tier Multiple Choice Diagnostic Test on the Angle Relationships - Desfi Ida Muryani; Padrul Jana; Sitti Mutia Umasugi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
Understanding the concept is one ability that students must master in learning mathematics because concepts in mathematics are related to each other. Based on the result of observation, it showed that not all students had a good conceptual understanding. Another finding reported that students had met the criteria for understanding concepts, not understanding concepts, and having misconceptions. The conditions where students experience misconceptions needto be considered because the misconception is a condition in which students use a concept that is not following the agreement of the expert with full confidence in the correctness of the concept. If misconception is allowed, it will affect the following concepts. This study aimed to determine the process and results of the analysis of student misconceptions and determined the causes of student misconceptions. The design of this research was descriptive qualitative with the number of subjects as many as 20 students. Data collection used a diagnostic test in the form of three-level multiple-choice questions and interview results. The methodused a test,an interview, and documentation. The steps in the data analysis of this research included data collection, data reduction, data presentation, and concluding. The validity test of the data used triangulation, namely, comparing the test results with the interview result. The research resultsshowed that there were students' misconceptions in the low and medium-level understanding group. Meanwhile, students in the high conceptual understanding group found False Positive criteria where false positives were parts of the misconception. However, in this study, the false positives were caused by students' inaccuracy in answering the questions. The causes of student misconceptions included using the concept of angles that were not following the agreement of the experts; applying angles with the wrong concept; wrong in interpreting images or just seeing based on images; wrong in algebraic addition arithmetic operations; wrongly applying the concept of angles in triangles, and not being careful in solving algebraic equations. <w:LsdException Locked=